International legal and methodological support of road traffic safety: concepts and essential features - Kolodyazhny, M. G. (Problems of legality, 2021)
The article aims to learn about international legal and international methodological support of road traffic safety and transport operation. A number of statistical indicators, which testify to the catastrophic state of road traffic safety both in the world in general and in Ukraine in particular, are presented. The development of the definition of this concept is proposed to carry out in the classical way: by highlighting its corresponding essential features. These include: object, subject, system and purpose. The object is the sphere of road traffic of the motor transport specifically. The subjects are the international institutions (UN, WHO, World Bank, etc.) and international public associations. The system of such support is classified into eight main groups according to the sphere of regulation of the relevant legal relations within the general sector of road traffic safety. In turn, the international methodological support in this sphere is classified into seven types according to its focus. The main international conventions, resolutions and other decisions, first of all, the UN’s ones, and the international agreements forming the system of the international legal support of road traffic safety are presented. The purpose of this support is to increase road traffic safety around the world. Hence, the international legal and methodological support for road traffic safety is a set of regulations of an international nature, information materials issued with the participation of official institutions with international status, as well as international public associations aimed at ensuring traffic safety, reducing mortality and road traffic injuries in different countries of the world.